Citizens' acceptance and use of new technology: the case of improved fuel in Ulaanbaatar - Batkhuyag, Undrakh (Frontiers in Sustainable Energy Policy, 2025)
IntroductionIn accordance with the government's pollution reduction policy, this study examines the acceptance and usage of improved fuel in a mandatory situation among citizens in Ulaanbaatar, Mongolia. The city struggles with air pollution due to high coal consumption, especially in its Ger districts.MethodsUtilizing the Unified Theory of Acceptance and Use of Technology (UTAUT) model, the research explores the determinants influencing the behavioral intention and actual use of improved fuel. The study integrates additional factors, namely environmental impact, risk perception, and autonomous as well as controlled motivation, into the UTAUT framework. Data was collected through a cross-sectional online survey of 198 adult residents.ResultsThe study identified performance expectancy, effort expectancy, and social influence as significant predictors of intention to adopt improved fuel. Performance expectancy had the strongest positive effect, while social influence negatively impacted intention, reflecting citizens' disapproval of improved fuel. Intention significantly predicted actual usage, but facilitating conditions were insignificant, likely due to the mandatory context. Autonomous motivation positively influenced intentions, highlighting the importance of understanding benefits. Controlled motivation, environmental impacts, and risks showed no significant effects.ConclusionThe findings underscore the importance of targeted policies and public awareness in enhancing the adoption of cleaner technologies to mitigate air pollution and improve public health in the city.